Homicide of children and adolescents in Mexico (1990–2013) - Frías, Sonia M. (International journal of comparative and applied criminal justice, 2018)
The trends and correlates of child and juvenile homicide rates in three developmental age groups (0-5, 6-11, and 12-17) during 1990-2013 in Mexico are examined by using vital statistical data. Homicide rates for adults and children were calculated yearly and the place where homicides occurred and the means used to commit homicide examined. Changes and continuities in homicide rates during 2002-2007 and 2008-2013 and their association with socio-economic, status of women, public security efforts, and firearm availability variables were studied. Homicide rates increased rapidly for adults and children in 2008 as did the rates in which a firearm was used. Rates for adults and children 0-5 years were particularly correlated. In some states, the youngest children’s rates increased by 75% or more than the rates for adults. High-increase states for younger children were closer to the U.S. border, were farther from abortion services, and had growing rates of female-headed households.